Peran Guru Dalam Mengatasi Kesulitan Membaca Al-Qur’an Pada Siswa di Sekolah Dasar Islam - Fusiroh, Fusiroh; Rokhmah, Siti; Rahman, Hendra Yulia; Taslim, Muhammad; Marhani (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
Teachers as an element in education not only play an important role as agents who provide knowledge but also as agents who provide assistance and support for students to overcome difficulties in the learning process. Teachers often become subjects, especially in discourses that discuss management, character building, and the effectiveness of the learning process so that the discourse of teachers as subjects who have a role in overcoming student difficulties tends to be neglected in scientific discussions. In line with that, this study focuses on the question "What is the role of teachers in overcoming students' difficulties in understanding and reading the Qur'an". To answer this question, this study used a descriptive qualitative approach by conducting observations and interviews with teachers and students. The findings in this study show that teachers have a crucial role in overcoming difficulties in understanding and reading the Qur'an among students in elementary schools. The role of teachers applied through personal approach, conducting learning evaluation, and providing interactive materials to students has been able to overcome students' difficulties in understanding and reading the Qur'an.